Implementation Of Monokrom Cafe Marketing Strategies On Social Media Instagram And Facebook - Faruk, Khofifah; Erlita, Erlita (SEAN Institute, 2024)
This research aims to determine the implementation of the Monochrome Cafe marketing strategy on social media Instagram and Facebook. This research applies qualitative methods with a descriptive approach. From this research it was found that due to the limited ability of business people to evaluate the effectiveness of implementing media marketing on Instagram and Facebook, the proposed strategy includes implementing appropriate analytical tools and metrics to track and evaluate social media marketing performance. With this approach, businesses can better understand the effectiveness of marketing strategies and make necessary adjustments to improve results. In this way, Monokrom Cafe can continue to develop and strengthen its position as an attractive culinary destination in the city of Ampana.